2009
DOI: 10.1007/s12185-009-0263-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of imatinib in a practical setting is correlated with imatinib trough concentration that is influenced by body size: a report by the Nagasaki CML Study Group

Abstract: Imatinib has dramatically improved long-term survival of chronic myelogenous leukemia (CML) patients. To analyze its efficacy in a practical setting, we registered most of CML patients in Nagasaki Prefecture of Japan. Of these, 73 patients received imatinib as an initial therapy. The overall survival rate of these patients was 88.7% at 6 years, and the cumulative complete cytogenetic response rate was 82.5% at 18 months. These results are comparable with the data of other reports including the IRIS study; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 17 publications
5
40
1
Order By: Relevance
“…The mean trough plasma IM level of patients administered 400 mg/day was higher in our analysis than that reported in a Western study (1058 + 557 ng/mL) [16,17]. A Japanese group reported a similar mean trough plasma IM level (1244 + 495 ng/mL) in Japanese patients with CML taking IM 400 mg/day, compared to our data (1378 + 725 ng/mL) [20]. Although BSA was not found to be a clinically significant determinant of the trough plasma IM level [10,11], the smaller body size of Asian patients as compared to Western patients might cause the difference in mean trough plasma IM level between Western and Asian patients with CML [20].…”
Section: Discussioncontrasting
confidence: 70%
“…The mean trough plasma IM level of patients administered 400 mg/day was higher in our analysis than that reported in a Western study (1058 + 557 ng/mL) [16,17]. A Japanese group reported a similar mean trough plasma IM level (1244 + 495 ng/mL) in Japanese patients with CML taking IM 400 mg/day, compared to our data (1378 + 725 ng/mL) [20]. Although BSA was not found to be a clinically significant determinant of the trough plasma IM level [10,11], the smaller body size of Asian patients as compared to Western patients might cause the difference in mean trough plasma IM level between Western and Asian patients with CML [20].…”
Section: Discussioncontrasting
confidence: 70%
“…This treatment failure may have been due to the standard dose of dasatinib not being tolerated. Some studies, including ours, reported that the amount of TKI administered in practice was often less than the standard dose [17,18,[35][36][37]. Therefore, tolerability for a standard dose must be considered when selecting a TKI.…”
Section: Discussionmentioning
confidence: 90%
“…5 Although several important clinical trials indicated that 400 mg of IM should be the standard daily dose for chronic phase CML patients, 1,2 in clinical practice, lower doses of IM are administered to B40% of Japanese patients. 6,7 This is largely because of the fact that for some Japanese patients, lower IM doses have sufficient trough concentration for therapeutic CML treatment. 7 Although this interindividual variability in IM pharmacokinetics is observed among Japanese CML patients, little is known about potential pharmacogenetic variation influencing IM metabolism and drug transport efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This is largely because of the fact that for some Japanese patients, lower IM doses have sufficient trough concentration for therapeutic CML treatment. 7 Although this interindividual variability in IM pharmacokinetics is observed among Japanese CML patients, little is known about potential pharmacogenetic variation influencing IM metabolism and drug transport efficacy.…”
Section: Introductionmentioning
confidence: 99%